KETERAMPILAN MEMBACA DAN MENULIS PERMULAAN MENGGUNAKAN MODEL VARK UNTUK SISWA SEKOLAH DASAR - Chandra Chandra; Mayarnimar Mayarnimar; M Habibi (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
The purpose of the development research is to produce a textbook on the development of Beginning Reading and Writing skills by using the VARK (Visual, Auditory, Read-Write, Kinesthetic) model in the practical grade I class. The development is based on the 4D (Define, Design, Develop, and Disseminate) models that emphasize the contextual user needs (teachers and learners), resulting in a draft of the Beginning Reading and Writing skills development package using the VARK model in class I elementary school , which contains the identification of competency standards and basic competencies, identification of indicators, identification of learning objectives. The results of the trial of practicality demonstrate that the textbook of Reading and Writing Beginnings by using VARK model in class I elementary school is practical and feasible to be used by grade 1 elementary school teachers.  Keywords: Beginning Reading and Writing skills, VARK model, Elementary School